2020
DOI: 10.3390/medicina56080415
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Traditional Cardiovascular Risk Factors Is Independently Correlated with Disease Activity in Patients with Psoriatic Arthritis

Abstract: Background and objectives: Psoriatic arthritis (PsA) is associated with several comorbidities, including among others an increased risk of cardiovascular (CV) disease, atherosclerosis, metabolic syndrome, hypertension dyslipidemia, and diabetes. The purpose of the present study was to determine how the number of CV risk factors correlates with disease related data such as disease activity. Materials and Methods: Cross-sectional study that encompassed 305 patients who fulfilled the CASPAR criteria for PsA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
8
2
Order By: Relevance
“… 42 Ferraz-Amaro et al have found a relationship between the presence of CV risk factors and increased inflammatory activity in a cross-sectional study of patients with PsA. 43 Although our results have suggested that uveitis is associated with higher inflammatory burden (reflected by a higher prevalence of sacroiliitis) we have not found a significant association between CV risk factors and uveitis.…”
Section: Discussioncontrasting
confidence: 79%
“… 42 Ferraz-Amaro et al have found a relationship between the presence of CV risk factors and increased inflammatory activity in a cross-sectional study of patients with PsA. 43 Although our results have suggested that uveitis is associated with higher inflammatory burden (reflected by a higher prevalence of sacroiliitis) we have not found a significant association between CV risk factors and uveitis.…”
Section: Discussioncontrasting
confidence: 79%
“…In a recent study, PsA patients with >3 CVD risk factors had the highest adjusted disease activity compared with those with fewer or no CVD risk factors. 22 Cardiometabolic conditions are over-represented in PsA and the prevalence of CVD risk factors was 73% in this cohort, compared with 50% in our study. While the different populations and disease outcomes studied limit our ability to make direct comparisons, these findings underscore the influence that burden of CVD comorbidity may exert on inflammatory arthritis course and is worthy of investigation in other RA and PsA cohorts.…”
Section: Discussioncontrasting
confidence: 58%
“…3 Additionally, several studies have suggested that the greater the disease activity, the greater cardiovascular (CV) risk, independent of disease duration and other demographic factors. 4 Disease Activity in Psoriatic Arthritis (DAPSA) score increases were associated with a higher number of CV risk factors. 4 In patients with established CVD (coronary artery disease, previous strokes, and/or myocardial infarctions), nonsteroidal antiinflammatory drugs (NSAIDs) pose a challenge.…”
Section: Resultsmentioning
confidence: 99%
“…4 Disease Activity in Psoriatic Arthritis (DAPSA) score increases were associated with a higher number of CV risk factors. 4 In patients with established CVD (coronary artery disease, previous strokes, and/or myocardial infarctions), nonsteroidal antiinflammatory drugs (NSAIDs) pose a challenge. 5 All NSAIDs confer the same risk of CV events, which should be considered when prescribing these drugs.…”
Section: Resultsmentioning
confidence: 99%